Food and nutritional security council: analysis of the social control over the food and nutritional security state policy in the State of Espírito Santo - Siqueira, Renata Lopes de; Fonseca, Débora de Andrade; Viana, Mariana Nogueira; Junqueira, Túlio da Silva; Ribeiro, Rita de Cássia Lanes; Cotta, Rosângela Minardi Mitre (Saúde e Sociedade, 2011)
Hunger, specific nutritional needs and all other forms of expression of food insecurity are not recent phenomena, nor is the concern about stanching them. The Food and Nutritional Security concept was reformulated and expanded over the years, and its current form aims not only to preserve, but also to expand the principle of social control regarding the formulation and monitoring of Food and Nutritional Security actions. The purpose of this study was to evaluate the social control of the Food and Nutritional Security Council of the State of Espírito Santo in relation to the FNS state policy, through the analysis of its internal regulations; the deliberations contained in the minutes of ordinary and extraordinary meetings of the council; and additional evaluation of the attendance of the entities' representatives. The predominance of deliberations about the organization of the structure and internal dynamics was observed, as well as reports on deliberations about the monitoring, proposals and FNS actions. There was also a significant amount of absences of civil and state entities' representatives at council meetings. It follows that although the Council represents an important strategy of social control in the pursuit of FNS state policies, this participation has not yet been fully carried out.